Simulation study on the carbon dioxide reforming of methane using hydrogen permselective membrane reactor - Tung, Chun Yaw (2005)
Carbon dioxide reforming of methane to syngas with H2/CO ratio of unity has received much attention in current catalytic research. However, the water formation and intensive energy requirement has limited its applicability for appropriate industrial practice. Accordingly, combined CH4 reforming with CO2 and O2 (CORM-POM) and the utilization of permreactor system have been introduced to overcome these problems. In this study, the model application of hydrogen permselective membrane reactor to promote equilibrium shifts of CH4-CO2 reforming processes was investigated. The thermodynamic equilibrium analysis indicated that the CORM process performance was in correspondence with temperature, but the H2/CO product ratio below unity was observed. Nevertheless, the addition of O2 in CORM process to improve the CH4 conversion and the H2 yield as well as to obtain H2/CO ratio of unity is theoretical feasible at selected temperatures and CH4:CO2:O2 feed ratios. Extended studies have been conducted to investigate the permreactor system application in promoting CORM reaction enhancements. The dynamic equilibrium results suggested that the reaction enhancements were influence strongly by the amount of hydrogen removal and the temperature is an important factor in determining the potential enhancement margins as the reaction-separation system operated at 900K exerts the most significant reaction enhancements. Besides, the H2/CO product ratio was improved close to unity for CORM reaction, while for combined CORM-POM the ratio was maintained at 1.0-1.2 with the utilization of permreactor system. In addition, the space velocity is an important factor to control the kinetic-transport behaviors in permreactor systems while the maximum attainable conversion and product yield levels were considerably determined by the sweep factor. The findings from dynamic equilibrium approach were confirmed by the kinetic-transport modeling results as the data obtained were well-match with the dynamic equilibrium approach. In short, the dynamic equilibrium technique can be useful diagnostic and optimization tool for membrane catalysis applications.